Firme-réseau globale et réseaux transnationaux d’ONG : Vers un nouveau mode de régulation ? - Florence Palpacuer (Revue de la Régulation)
Global network firm and GLOBAL NGO networks: towards a new mode of regulation? The paper draws on the case study of an activist campaign against the German brand PUMA regarding work conditions at a subcontracting factory in Mexico, to develop an analysis of the strategic and organizational transformations underlying relationships between firms and non-governmental organizations (NGOs). It is argued that strategic and organizational changes in transnational NGO networks share core characteristics with the global production networks developed by large corporations. The concept of a mode of regulation is used to put such changes in the broader perspective of stabilizing social conditions in the global economy.